The Analysis of Elementary School Students' Concrete Operational Thinking In Islamic Learning - Fatmawati; Amini; Nurzannah (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
Concrete operational thinking skills are important for elementary school students to understand religious concepts. There are still difficulties in applying these concepts in everyday life, including in Islamic Religious Education subjects. This study aims to analyze the concrete operational thinking of elementary school students in Islamic religious learning. The background of this study is multi-site at SDN 101933 Perbaungan, SDN 101929 Perbaungan, and SDN 108293 Perbaungan. This study uses qualitative with case study method in revealing natural phenomena in schools. Data acquisition using observation, interview and documentation methods. Data analysis is done inductively, namely by analyzing the data as a whole to then draw conclusions. Data validity testing uses research data triangulation techniques. The results of this study concluded that students' thinking in Islamic Religious Education learning in the three schools was at the concrete operational stage. However, when faced with abstract concepts such as spiritual meaning or deeper ethical values, students showed difficulty in linking these concepts to real-life situations. The method used by teachers is to use a more interactive, experience-based and contextual learning approach to help students connect religious concepts with everyday life.